Republic of Lithuania : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that impressive growth continued unabated in Lithuania in 2004. GDP expanded by an estimated 6 3/4 percent in 2004, driven by vigorous private consumption and investment growth. The unemployment rate declined to 10 1\2 percent of the labor force but bottlenecks have developed in certain sectors, exacerbated by migration flows to the European Union (EU) and the United States. Structural reforms continued in 2004, but deeper reforms remain necessary to keep Lithuania on a real convergence path with the EU.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet